DIAGNOSIS OF HERPES VIRUS INFECTION - Khazhimatova Guzal Marufzhanovna (Galaxy International Interdisciplinary Research Journal, 2023)
Today, it is generally accepted that the herpes simplex virus can affect various organs, and its significance in carcinogenesis and secondary infertility has been proven. Increasingly, there are reports about the role of the virus in the pathology of the liver, brain, prostate, diseases of other systems.